Inter population variability of frost-resistance in provenances of scot pines (Pinusylvestris L.R. hamata Steven) in Turkey - Özel, Halil Barış; Ayan, Sezgin; Isajev, Vasilije (National Library of Serbia, 2016)
Frost-resistance variability of Scotch pine (Pinus sylvestris L. var. hamata Steven) seedlings grown in nurseries conditions, originated from 10 provenances, have been analyzed. The provenances from Black Sea region, Central Anatolian region and Eastern Anatolian region in Turkey have been used in selection of seed zones. The results of frost-resistance tests indicated a strong relationship of implemented freezing degrees with injury degrees of Scotch pine needles and photosynthetic productivities. On the other hand, another significant relationship has been determined between chlorophyll fluorescence and ion leakage methods (r=-0.801). This result shows that those two methods can be safely used in determining the damages due to low temperatures. In frost resistance tests, Scotch pine seedlings from different provenances have been frozen at -10, -20, -30 and -40?C. According to the Duncan test results, it has been determined that damage increased as temperature decreased. The damage level at -10?C implementation is 3.5% which can be tolerated by plants. But when the temperature has been decreased to -20?C, the level of damage has increased to 51.25%. As a result of photosynthetic analyses in this phase, it has been determined that there is a statistically significant relationship between provenances and temperature levels. Under the light of those findings, they have determined that the photosynthetic productivity has significantly decreased at temperatures between -20?C and -40?C. This situation conforms to injury index values determined in this study. As a result of injury index and photosynthetic productivity tests used for determining the damage after frost-resistance tests, it has been determined that the provenances of Amasya-Kunduz, Bolu-Alada?, D?zce-Y???lca, Samsun-Vezirk?pr? and Eski?ehir-?atac?k are more sensitive to frost than other provenances.
Keywords: Frost Damage; Provenances; Injury Index; Plant Science; Scotch Pine; Photosynthetic Activity; 15. Life on land